Relapse of Acute Myeloid Leukemia with t(16;21)(p11;q22) Mimicking Autoimmune Pancreatitis after Second Allogeneic Bone Marrow Transplantation. (10th January 2011) - Kamada, Yuhei; Suzukawa, Kazumi; Taoka, Kenichi; Okoshi, Yasushi; Hasegawa, Yuichi; Chiba, Shigeru
Abstract : We report the case of a 37-year-old woman who had a relapse of acute myeloid leukemia (AML) during treatment for chronic graft versus host disease (cGVHD) after allogeneic bone marrow transplantation. She was originally suspected of having autoimmune pancreatitis. Relapse of AML often occurs at extramedullary sites. Whereas the pancreas is rare as an organ of AML relapse, physicians should be aware that enlargement of the pancreas could be a sign of relapsed AML when excluding autoimmune pancreatitis, particularly during active cGVHD after allogeneic stem cell transplantation.